القواعد الناظمة لشركة المضاربة بين النظرية والتطبيق القضائي: دراسة مقارنة بين القانونين الفلسطيني والأردني - Anas Abu Musa Aloun (Malaysian Journal of Syariah and Law)
Speculative contract is one of the common contracts in practical reality, where a person who owns cash capital or other assets resorts to a merchant and delivers this capital to him for development and investment, and the reason for this contract is either that the owner of capital does not know trade and seeks to achieve profit and investment, or that he wants to increase his income without exerting effort, and we are here before a type of companies but this company has a special nature that does not comply with the rules stipulated in Decree-Law No. 42 of 2021 regarding companies, but rather complies with civil law rules. The research aimed to know the position of the judiciary from the multiple problems raised by the provisions of this contract from its validity, adaptation, distinction from other contracts and termination, and the researcher followed to reach the desired goal an analytical and comparative approach between Palestinian and Jordanian law, and concluded that there are basic controls that must be adhered to by contractors when concluding a speculative contract otherwise invalidity or corruption or conversion of contract into work or lease contract will result, as well as taking into account specific controls when terminating otherwise bearing responsibility for damage by arbitrary termination.